Prophetic-Based Character Education Management in Improving the Quality of Graduates: (A Multi-Site Study at Pondok Pesantren Pembangunan Al Fattah Kikil and Pondok Pesantren Pembangunan Al Fatahiyah) - Alif Fatkhur Rohman; Akhyak Akhyak; Asrop Safi’i (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This dissertation, titled